Improving Architecture Students' Design Skills: A Studio Experience. (28th February 2022) - Ceylan, Salih; Soygenis, Sema
Abstract: Design is a complicated task that requires the simultaneous operation of different cognitive processes. Many researchers claim that the design process is something that can be supported with various implementations. Design education helps students improve their design skills by utilising different types of exercises. This article presents a case study wherein third‐year undergraduate students at an architecture school's design studio were the subjects. The normal workflow of the studio was reinforced with checkpoints where the students were asked to complete exercises based on sketching, writing and visual analogy. The aim of the case study was to stimulate different cognitive processes in the students' brains through structured exercises to support their design process. This study questions the interrelation between each cognitive process and their relationship with the overall design process, plus whether verbal and written tasks as well as sketching, as cognitive exercises, contribute to the design process. The case study's findings indicate that students derived significant support from the exercises, and that there is correlation between the students' participation level in the exercises and their success in the design task. The case study also shows the interrelation between the writing and sketching exercises and their effects on the students' success in the design process. This article suggests that design educators would benefit from structuring methods efficiently in order to achieve better results when training neophyte designers.